Assessment of flood storm scenarios for Tasik Kemajuan, UTHM using HEC-RAS - Kasmin, H; Mohamad Razi, M A; Adnan, N A S; Tan, L W
Batu Pahat was hit by a significant flood in year of 2023; however, the area within the Universiti Tun Hussein Onn Malaysia (UTHM) was spared, in contrast to what occurred in 2006/2007. Thus, this study aims to examine the current storage of Tasik Kemajuan, one of UTHM's control structures, and to simulate this pond using several flood scenarios in HEC-RAS software. The study employs the cross-sectional data of Tasik Kemajuan from the previous study. Rainfall intensities under several flood storm scenarios were obtained based on calculation of three approaches i) highest rainfall events occurred of the nearest station; ii) typical return periods recommended by the MSMA Guidelines and iii) assumed peak runoff. By using Surfer Software, Tasik Kemajuan shows its current water volume of 12723.85 m3. Flood simulation shows that the lake has the potential to become flooded when the lake receives rainfall intensity of 96.6 mm/hr with peak flow of 15 m3/s; and above. IDF curve observation shows that rainfall intensity of 96.6 mm/hr has return period of larger than 500-yrs ARI, which is quite impossible to occur at the nearest time. These insights are essential for formulating efficient water resource management strategies, therefore aiding in the sustainable management of Tasik Kemajuan and its surrounding environment